Incipient fault detection of the high-speed train air brake system with a combined index. (July 2020) - Ji, Hongquan; Zhou, Donghua
Abstract: Reliability of the high-speed train air brake system is very critical to ensure a safe and comfortable operation environment for passengers. In our recently published work, a new monitoring strategy based on the concept of inter-variable variance (IVV) was proposed. It was illustrated by theoretical analysis and extensive experiments that this strategy is effective for several kinds of faults, and superior to the KNORR logic which is adopted by most high-speed trains in practice. However, the aforementioned strategy based on conventional IVV still suffers from two drawbacks. More specifically, due to the specific property of IVV, this strategy is unable to detect certain faults even if the fault is very serious; in addition, the detectability of conventional IVV for incipient faults with relatively small magnitudes still needs to improve. In this paper, a fault detection method incorporating the idea of four stages partition and involving a new combined statistic is presented to perform fault detection for high-speed train air brake systems. Through theoretical reasoning, it is pointed out that the proposed method can overcome drawbacks of the conventional IVV method to a large extent. To demonstrate the effectiveness and merits of the proposed fault detection method, in comparison with existing methods, experimental studies are carried out on a practical high-speed train air brake test bench. Highlights: A novel fault detection index is proposed to monitor the air brake system. The index can detect some faults that cannot be detected by existing methods. The index is more sensitive to several kinds of incipient faults. Practical experiments are carried out to demonstrate the effectiveness.